IMPLEMENTASI KEBIJAKAN PENANGGULANGAN HIV/AIDS DI KOTA MANADO - AMU, IRFAN; LENGKONG, FLORENCE; TAMPI, GUSTAAF (Sam Ratulangi University, 2020)
HIV control in Indonesia has been noted to have improved from it’s implementation. Various HIV serviceshave grown and the number of people using them has also increased rapidly. This led the Health Ministerissued a Health Minister Regulation No. 21 of 2013 on HIV/AIDS prevention. But, as practice, every regionhas a yearly rise in HIV/AIDS cases. The purpose of the study is to find out how implementation of theHIV/AIDS prevention policies in Manado can be. The experimental concept used in this research is to takea kind of qualitative research with a descriptive approach. Then data-collection techniques will done byinterviews, observations and documentaries. The technique for data-analysis in this research used Miles'and hubennan's qualitative data analysis. The results showed that the implementation of HIV / AIDSprevention policies in Manado was classified as good in terms of communication between the governmentand the targets that had been carried out, but for human resources in HIV/AIDS prevention it was stillconsidered to be less than optimal. Whereas with a very supportive sense of execution, and SOP thatconforms to health care standards and has associated coordination with stakeholders. So it should beconcluded that the implementation of the HIV/AIDS prevention policies in Manado has not been fullyimplemented.Keywords : Policy Implementation, Prevention, HIV / AIDS